Trabalho e luta por reconhecimento: a identidade do trabalhador com deficiência - Lara, Andrea Paula dos Santos (2011)
This study aims to identify the impacts of recognition and situations of disrespect of the labor market in the constitution of the identity of the disabled worker and the meanings of metamorphosis caused in the midst of this form of relationship, and to evaluate possible alternatives for emancipatory movements of workers with disabilities in this situation. Our main theoretical theories were: Identity and Metamorphosis, by Antonio da Costa Ciampa; Recognition and disrespect, by Axel Honneth, and the concept of social empowerment of Jurgen Habermas. We use the method of the life history, as allowed us to verify the uniqueness of an individual and the aspects related to issues pertaining to the vast majority of people with disabilities in our society; finally, this material has enabled us to realize that both the recognition of situations how much disrespect experienced by the individual, can leverage significant disruptions with characters and fetishistic situations in which recognition occurs favoring the emergence of internal resources capable of directing the metamorphosis of individual emancipation, without, however, be sufficient when it comes to fighting for recognition, because this fight is only effective when there is sharing the feeling of disrespect and is generated, thus a collective movement towards changing the social reality